Komunikasi Suami Istri Sebagai Upaya Pengutan Dukungan Emosional Dalam Membangun Keharmonisan (Sebuah Studi Pastoral Di Stasi Sta. Elisabeth Lewokung Paroki Sta. Maria Diangkat Ke Surga Lewokluok-Bama) - Rekoruja, Ursula Nogo; Lelu, Skolastika; Aran, Alfonsus Mudi (Publikasi Indonesia, 2025)
The purpose of this study is to find out the understanding of communication and analyze the factors that affect the communication of husband and wife at Sta. Elisabeth Lewokung Station, to find out efforts to strengthen emotional support in building harmony at Sta. Elisabeth Lewokung Station, and to find out the efforts of husband and wife harmony in Sta. Elisabeth Lewokung Station. In this modern era, the challenges and dynamics of life are increasingly complex, strengthening emotional support through effective communication is of paramount importance. The method used in this study is a qualitative descriptive method, using data collection techniques in the form of observation, interviews, and documentation. The research was carried out from February to May 2025. The results of this study found that communication between husbands and wives at Sta. Elisabeth Lewokung Stasi in the family became less intense as a result of the emergence of conflicts in the family, thus causing disharmony in the relationship between husband and wife. Conflicts that arise in the family are caused by economic factors, which cause a loss of trust between each partner in the family as a result of a lack of openness, empathy and lack of support from one party in the family. In addition, there is a lack of mutual understanding, mutual acceptance of reality, and self-adjustment between married couples at Stasi Sta Elisabeth Lewokung.